Candida albicans necrotizing fasciitis following cosmetic tourism: A case report - Roberta Gilardi; Paola Parisi; Luca Galassi; Guido Firmani; Massimo Del Bene (JPRAS Open, 2023)
Background: Necrotizing fasciitis is a rare and potentially life-threatening soft tissue infection, even more so when associated with fungal causative agents. Onset has been identified in nosocomial settings following elective surgery, but not in esthetic surgery. Case presentation: We here present a case of necrotizing fasciitis related to Candida albicans infection which occurred in an immunocompetent patient who received a cosmetic breast augmentation mastopexy combined with a Brazilian Butt Lift using autologous fat grafting. The case was managed with aggressive wound exploration and debridement. Treatment was delayed by the diagnostic challenge and the difficulty in identifying the causative agent, but the patient fully healed and recovered once the C. albicans was isolated in culture tests and appropriate antimycotic treatment was implemented. Conclusion: Considerations should be made regarding the possibility of implementing an antimycotic option for first-line empirical treatment despite the rarity of fungal etiology because of the threat of diagnostic delay and worse outcome.